2007
DOI: 10.1016/j.ijgo.2007.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional transrectal ultrasonography in adolescent patients with polycystic ovarian syndrome

Abstract: These findings indicated that, in adolescent patients, 3D-TRS combined with transabdominal ultrasonography can improve the precision of the diagnosis of PCOS. The S/A ratio may become the ultrasonographic diagnostic marker for PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Overall, nine studies conducted between 2003 and 2013 were identified, and seven were used in this review (8)(9)(10)(11)(12)(13)(14). Two studies were excluded from our analysis because there was a lack of ultrasonographic quantitative data (15,16).…”
Section: Results Of Ovarian Ultrasound Studies In Adolescentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, nine studies conducted between 2003 and 2013 were identified, and seven were used in this review (8)(9)(10)(11)(12)(13)(14). Two studies were excluded from our analysis because there was a lack of ultrasonographic quantitative data (15,16).…”
Section: Results Of Ovarian Ultrasound Studies In Adolescentsmentioning
confidence: 99%
“…Group A included five studies, which had PCOS adolescents with or without controls and used 2D ultrasound (9-11, 13, 14). Group B included two studies, which consisted of both adolescents and young women and used 2D and 3D ultrasound (8,12).…”
Section: Results Of Ovarian Ultrasound Studies In Adolescentsmentioning
confidence: 99%
See 3 more Smart Citations